The orthosteric GABAA receptor ligand Thio‐4‐PIOL displays distinctly different functional properties at synaptic and extrasynaptic receptors. (1st October 2013) - Hoestgaard‐Jensen, K; O'Connor, R M; Dalby, N O; Simonsen, C; Finger, B C; Golubeva, A; Hammer, H; Bergmann, M L; Kristiansen, U; Krogsgaard‐Larsen, P; Bräuner‐Osborne, H; Ebert, B; et al.
Abstract : Background and Purpose: Explorations into the heterogeneous population of native GABA type A receptors (GABAA Rs) and the physiological functions governed by the multiple GABAA R subtypes have for decades been hampered by the lack of subtype‐selective ligands. Experimental Approach: The functional properties of the orthosteric GABAA receptor ligand 5‐(4‐piperidyl)‐3‐isothiazolol (Thio‐4‐PIOL) have been investigated in vitro, ex vivo and in vivo . Key Results: Thio‐4‐PIOL displayed substantial partial agonist activity at the human extrasynaptic GABAA R subtypes expressed in Xenopus oocytes, eliciting maximal responses of up to ∼30% of that of GABA at α5 β3 γ2S, α4 β3 δ and α6 β3 δ and somewhat lower efficacies at the corresponding α5 β2 γ2S, α4 β2 δ and α6 β2 δ subtypes (maximal responses of 4–12%). In contrast, it was an extremely low efficacious agonist at the α1 β3 γ2S, α1 β2 γ2S, α2 β2 γ2S, α2 β3 γ2S, α3 β2 γ2S and α3 β3 γ2S GABAA Rs (maximal responses of 0–4%). In concordance with its agonism at extrasynaptic GABAA Rs and its de facto antagonism at the synaptic receptors, Thio‐4‐PIOL elicited robust tonic currents in electrophysiological recordings on slices from rat CA1 hippocampus and ventrobasal thalamus and antagonized phasic currents in hippocampal neurons. Finally, the observed effects of Thio‐4‐PIOL in rat tests of anxiety, locomotion, nociception and spatial memory were overall in good agreement with its in vitro and ex vivo properties. Conclusion and Implications: The diverse signalling characteristics of Thio‐4‐PIOL at GABAA Rs represent one of the few examples of a functionally subtype‐selective orthosteric GABAA R ligand reported to date. We propose that Thio‐4‐PIOL could be a useful pharmacological tool in future studies exploring the physiological roles of native synaptic and extrasynaptic GABAA Rs.